Variação espacial e temporal na estrutura do habitat e prefência de microhabitat por pequenos mamíferos na Mata Atlântica - Freitas, Simone Rodrigues de (1998)
Nowadays studies on habitat choice have been worried with scale problems, as spatial as temporal scale. This work was carried out in Guapimirim (22°29'S e 43°00'W), Rio de Janeiro State from February'97 to February'98. The study area is a vicinity of Serra dos Órgãos National Park at Atlantic Forest and is occupied by several houses that can influence somehow animal and plant communities. This work is divided in four main topics: concepts definition, new method description, effects of spatial and temporal scales on habitat structure, and microhabitat choice by small mammals. First different concepts of habitat used were discussed through a brief historie, then a new definition of habitat distinguishing it from niche and biotipe concepts is presented. Therefore a new method to measure microhabitat structure was proposed showing the advantages - simplicity, quickness, practicality and repeatability. The scale problem on habitat structure was discussed after. Spatial and temporal dynamics of microhabitat and mesohabitat structures, and of litter production, that must be considered in habitat preference studies on small mammals was discussed. Finally microhabitat preference by small mammals was studied through logistic regression, seeking for a pattem of species occurrence in the study area.